1991
DOI: 10.1002/bit.260380602
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling cell proliferation and antibody production in mouse hybridoma cells: I. Influence of the amino acid supply

Abstract: To investigate the influence of medium amino acid resources on hybridoma cell proliferation and monoclonal antibody secretion, we first determined, in two different cell lines, the pattern of amino acid consumption. We then showed that complementation of each cell line by an amino acid solution prepared to cover its needs led in both cases to a marked increase in cell density and monoclonal antibody production. This observation suggests that the amino acid supply is one of the factors limiting cell growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 32 publications
(2 reference statements)
2
67
0
2
Order By: Relevance
“…A possible explanation of these results might be that dietary methionine and threonine may have interfered with apoptotic or necrotic process of bursal lymphocytes during infection of IBDV because the use of IBD vaccine can cause a varying degree of bursal lymphocytolysis (Amakye-Anim et al, 2000). Through protein synthesis and cellular signaling mechanisms, addition of threonine to the culture medium prevented apoptosis, stimulated cell growth and promoted antibody production in lymphocytes (Duval et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of these results might be that dietary methionine and threonine may have interfered with apoptotic or necrotic process of bursal lymphocytes during infection of IBDV because the use of IBD vaccine can cause a varying degree of bursal lymphocytolysis (Amakye-Anim et al, 2000). Through protein synthesis and cellular signaling mechanisms, addition of threonine to the culture medium prevented apoptosis, stimulated cell growth and promoted antibody production in lymphocytes (Duval et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary levels of certain individual amino acids have been shown to affect immune response (Jeevanandam et al 1990;Paaw and Davis, 1990). Methionine (Swain and Johri, 2000;Rama Rao et al, 2003;Shini et al, 2005) and threonine (Duval et al 1991;Ball et al, 1999) are two amino acids that have proven immune regulatory action. There is some evidence that essential amino acid level in the feed higher than of NRC specifications needed to achieve optimal immune system and growth performances (Quentin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Duval et al (1991) also observed that addition of all consumed amino acids resulted in increased growth and antibody production, while selective addition of only four of the most rapidly consumed amino acids did not increase cell concentration or extend the life span of the culture. This will be discussed in Chapter 8.…”
Section: Glutamine-fed Batch Culturementioning
confidence: 84%
“…Therefore an experiment was set up in which batch cultures of NB1 hybridoma cells were supplemented with double the concentration of these particular amino acids. Duval et al (1991) showed that for their particular cell line vitamins were a limiting nutrient in batch culture. Therefore a batch culture of NB 1 hybridoma cells was also set up in which the vitamin concentration was doubled.…”
Section: Introductionmentioning
confidence: 99%